A study of university staff in relation to the alignment of organizational environment and informal learning - Frock, David J., author; Lynham, Susan, advisor; McKelfresh, David, advisor; Smith, Ken, committee member; Warner, Mark, committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: informal learning; organizational environments; student wellness; training and development; university administration